Successful endoscopic mechanical lithotripsy for post-ERCP gallstone ileus: a case report - Jing Wang; Jing Wang; Zhe Luan; Bin Yan; Gang Sun (Frontiers in Medicine, 2025)
Gallstone ileus is a rare but severe complication of gallstone disease and is typically caused by the formation of a fistula between the biliary and gastrointestinal systems. The conventional treatment approach is enterolithotomy with stone removal. However, for elderly patients or those with underlying comorbidities, surgical intervention poses significant risks. Therefore, exploring minimally invasive, nonsurgical treatment strategies holds critical clinical value. A 63-year-old female was admitted to the hospital due to abdominal pain, chills, and high fever. She was diagnosed with a large common bile duct stone (diameter 3.9 cm). During endoscopic retrograde cholangiopancreatography (ERCP), as the stone was too large to be removed directly, endoscopic sphincterotomy (EST) combined with the placement of a biliary plastic stent was performed. On the 7th postoperative day, the patient developed nausea, vomiting, and constipation. Laboratory tests revealed elevated inflammatory marker, pancreatic enzyme, bile enzyme, and bilirubin levels. Imaging studies revealed intestinal dilatation and a high-density shadow within the intestinal lumen, leading to the diagnosis of gallstone ileus. On postoperative day 11, biliary and pancreatic stents were placed. On postoperative day 16, endoscopic stone extraction was attempted, successfully relieving the obstruction. The patient recovered well postoperatively and experienced no recurrence during the 2-month follow-up. This case report describes the successful treatment of post-ERCP gallstone ileus using endoscopic stone extraction and fragmentation techniques.